Advanced Health Technology Managing Risk While Tackling Barriers to Rapid Acceleration. - Douville, Sherri (Milton : Productivity Press, 2023)
This book helps readers understand how to manage and transcend risks to drive the Quadruple Aim of improved patient experiences, better patient and business outcomes, improved clinician experience, and lower healthcare costs.
Next Steps: Team Training to Bust Medical (and Medical Technology) Misinformation -- References -- Part II Management and Leadership Competencies and Objectives for Driving the Science, Medicine, and Engineering of Advanced Medical Technology Forward -- Chapter 4 Allyship in Reducing Medical Technology Risk: Why Partnerships Are Vital to Your Professional Success -- Introduction -- Prelude -- Aligning Allies with Reducing Risk and Increasing Success -- Pros and Cons of Allies -- Evidence That Ally Relationships Work -- Recognizing, Recruiting, and Empowering Allies
Description based upon print version of record.
Putting Myself in the Shoes of a Leader Looking to Learn How to Recognize a Solid Ally
OCLC-licensed vendor bibliographic record.
Keywords: Medical technology -- Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Development / Business Development